A Theoretical Insight into the Mechanism of Cu(I)‐Catalyzed CN Coupling between Aryl Halides and Aqueous Ammonia. Issue 8 (12th August 2015) - Chen, Ting; Yan, Mingkuan; Zheng, Chao; Yuan, Jie; Xu, Shen; Chen, Runfeng; Huang, Wei
Abstract Computational investigations of Cu(I)‐catalyzed CN coupling between aryl halides and aqueous ammonia without addition of any base or ligand were reported. Density functional theory calculations were performed to reveal the mechanism of the ligand‐free amination reaction for the preparation of primary aromatic amines. Through systematic evaluation of the relative concentrations of possible Cu species in solution, we propose that the active catalyst is the neutral Cu(I) complexes rather than the Cu(I) cations; oxidative addition of aryl bromide is a facile step of the catalytic cycle; reactant (NH3) and solvent molecule (NMP) can act as ligands of Cu species to help reduce the activation energy of the forward reaction and increase the activation energy of the reverse reaction; except for Pathway B, the deprotonation step is irreversible due to the extreme exothermic feature; the elimination of H2O is kinetically favored, while that of HBr is thermodynamically preferred. These findings should be valuable for the mechanism understandings of the ligand‐free Cu‐catalyzed CN cross‐coupling reactions and for the further development of highly efficient amination catalyst systems.